2019
DOI: 10.3389/fpls.2019.01514
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Comparisons of Mutations Induced by Carbon-Ion Beam and Gamma-Rays Irradiation in Rice via Resequencing Multiple Mutants

Abstract: Physical mutagens, such as carbon-ion beams (CIBs) and gamma rays (GRs), induce mutations with high frequency at a relatively low dose and are more user-friendly and environment-friendly in mutation breeding. Previous studies showed that CIBs induced large sized deletions and insertions, and chromosomal rearrangements, whereas GRs induce shorter deletions and insertions, and more frequent base substitutions. However, the difference on the genomic level between CIB- and GR-induced mutations remains to be clarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
52
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 59 publications
12
52
1
1
Order By: Relevance
“…Overall, under 40 Gy or 80 Gy, single-base substitutions (SBSs) were the main mutation types induced by CIB irradiation. Moreover, CIB irradiation also induced a number of InDels, and short ones (<5 bp) were more prevalent than large ones, which is in accordance with the findings of previous studies [ 15 , 16 ]. Among CIB irradiation-induced SBSs, we detected a bias towards C:T and A:G transitions and observed a higher overall frequency of CIB irradiation-induced transversions versus transitions ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, under 40 Gy or 80 Gy, single-base substitutions (SBSs) were the main mutation types induced by CIB irradiation. Moreover, CIB irradiation also induced a number of InDels, and short ones (<5 bp) were more prevalent than large ones, which is in accordance with the findings of previous studies [ 15 , 16 ]. Among CIB irradiation-induced SBSs, we detected a bias towards C:T and A:G transitions and observed a higher overall frequency of CIB irradiation-induced transversions versus transitions ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…Those authors suggested that mutation frequency may be a good indicator for sequencing-based determination of the optimal irradiation conditions for inducing mutations. Using whole-genome resequencing, researchers conducting two recent independent studies compared and characterized mutations induced by CIB irradiation and GRs in rice ( Oryza sativa L.) [ 15 , 16 ]. Both studies showed that SBSs were the most abundant type of mutation induced by the two mutagens.…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with the sequencing data for 1504 rice mutants, in which a wide range of mutations was observed across the mutant plants [42]. Moreover, genome-wide comparisons using resequencing was performed by Yang et al [43], to compare four mutant rice plants induced by 250 Gy gamma radiation. The results showed that the individual mutants had different total numbers of mutations and proportions of mutation types.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, high-LET irradiation also typically leads to larger deletions and more complex DNA rearrangements than low-LET irradiation, which may derive, at least in part, through the action of an alternative end-joining repair pathway in these instances (Hirano et al, 2015). In rice, tens up to hundreds of thousands of SNVs and indels, along with 0 to approximately 11,000 structural variations (SVs), have been observed per mutant plant following treatment with ionizing radiation (Table 1; e.g., Cheng et al, 2014;Zhenga et al, 2017;Li, Shimizu, et al, 2019;Yang et al, 2019;Hwang et al, 2020).…”
Section: B Random Mutagenesismentioning
confidence: 99%